ANALISIS KEARIFAN LOKAL TANAMAN KARET DI KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Agus Riawan; Eri Sayamar; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research was conducted in the subdistrict. Logas Tanah Darat. Kuantan Singingi regency the village as a study option that Sikijang Village and the Village Stop area. This study aims to identify local wisdom ever in industry rubber farmer, analyze the application of local wisdom that are still ongoing in rubber farming in the subdistrict Logas Tanah Darat, knowing the application of environmentally friendly local wisdom in the use and management of farming rubber. Benefit in this study are can collect and recalls the old culture that has been lost, and that is still there so it can be used as reference material for the future.Technical sampling in this study using snowball sampling technique or done in sequence to ask for information on people who have been interviewed or contacted earlier, so on. And data collection techniques used in this study are indepth interviews with key informants and kuesioner. Analysis data using descriptive methods local kualitatif. Wisdom is a form of knowledge, beliefs, rules, customs, and habits conducted by a society that respects the norms and values of the culture that has been there earlier and passed down by ancestors to be passed on to children and nephew in the running of everyday life. In this study there is a local wisdom in the cultivation of rubber, of which 80% of the people are farmers rubber. Case proved that they still run a local wisdom passed down there with them, even though the procedure, the customs and rules is not running as before. Local wisdom rubber plants totaling 81 local knowledge, which is never a farmer and formerly amounted 45 and is done now amounted 4. Local wisdom farmers who never existed and do farmers first, and is still used by farmers are now amouted 32 local wisdom. Keywords: Local Wisdom, Rubber, and the Environment